Sikap Wara' Seorang Siswa: (Studi dalam Kitab Ta'lim Muta'allim Karya Az-Zarnuji) - M. Abdul Aziz; Martoyo Martoyo (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This article discusses the importance of a wara' attitude in seeking knowledge according to Shaykh Az-Zarnuji in the book Ta'lim Al-Muta'allim. Islamic education emphasizes the development of morals and behavior based on Islamic values. The wara' attitude, namely the attitude of being careful about halal and haram and avoiding things that are doubtful, is identified as the key to obtaining maximum benefit from the knowledge learned. This attitude involves guarding against overeating, oversleeping, useless talking, consuming market food, and associating with destructive people. By adopting a wara' attitude, a student can increase concentration, understanding and blessing in the knowledge he is studying.